Limitations of graphical procedures based on excluded-volume theories for the determination of Kθ - Shashikant S.; Patel C.K.; Chaturvedi P.N. (My University, 2025)
The [η]-M relations of some commonly used two-parameter excluded-volume theories have been considered in regard to estimating Kθ, a measure of unperturbed dimensions of polymers. Limitations of these theories have been demonstrated using [η]-M data of two substituted acrylamide polymers, poly(N-phenyl acrylamide) (PNPA) and poly(N-(p-methyl)phenyl acrylamide) (PNPMPA), which range in their v values from flexible to semi-rigid chain character. The analysis shows that the theories fail to accommodate any such set of [η]-M data that leads to v values larger than its prescribed limit in the corresponding theory. For the Flory-Fox-Schaefgen and Domb-Barrett theories vmax came out to be 0.80; and for the Kurata-Stockmayer-Roig, Burchard-Stockmayer-Fixman and Inagaki-Ptitsyn theories it extended to unity. As a consequence of the failure of these theories, two more equations due to first-order perturbation and Bueche-James theories were invoked with a view to extending the scope of this analysis. The upper limit of v was thus extended to 1.25 and 2.00, respectively. These theories were found to be of general applicability. The values of Kθ estimated by appropriate methods were 4.65 × 10-4 and 8.5 × 10-4 dl mol 1 2 g -3 2 for PNPA and PNPMPA, respectively. © 1992.